Conducting formulation - James,M; McCulloch,I; Duffy,W; May,PE; Walker,D; Waller,DP; Childers,RK; Rodman,SE (2009)
The invention relates to novel formulations comprising an org. semiconductor (OSC) and a conductive additive, to their use as conducting inks for the prepn. of org. electronic (OE) devices, esp. org. photovoltaic (OPV) cells, to methods for prepg. OE devices using the novel formulations, and to OE devices and OPV cells prepd. from such methods and formulations.